Pension Regimes and Saving - Cuevas, Alfredo (Occasional Papers; Occasional Paper, 1997)
Public pension systems around the world have been criticized in recent years for some serious flaws, including the excessive burden they impose on the public finances and their depressing impact on saving rates. This study analyzes the impact of pension systems and pension reform on saving, paying particular attention to the impact of the introduction of defined-contribution plans like that of Chile. It also surveys the literature on the impact of pension regimes on saving, discusses some recent reforms, and addresses the role of private pension plans.